Strategi Implementasi Produksi Bersih untuk Meningkatkan Kinerja Industri Gondorukem (Studi Kasus Nagreg Jawa Barat) - Kharismawati, Dyah; Indrasti, Nastiti Siswi; Suprihatin, Suprihatin (Universitas Brawijaya, Indonesia, 2016)
This study aimed to audit environmental performance in gondorukem (resina colophonium) industry, analyze the main problem of waste and formulate the direction of industry development by cleaner production method. Data collection was conducted by field observation, interview and expert surveys. The analysis method used in this research is cleaner production audit which consist quick scan on stages of production process and formulation the cleaner production option, continued prioritization with Analytic Hierarchy Process. This study was case study take place in nagreg west java. Results of the analysis showed that scheduling sap delivery to be a priority based alternative with the largest value analysis id 0,216 compared with other alternatives.